Pengaruh Motivasi dan Insentif Terhadap Kinerja Karyawan Bagian Merchandise Counter (Pramuniaga) di PT. Matahari Department Store Mall of Serang - Yuli Subihawati; Munirah Munirah; John Chaidir (Prosiding Amal Insani Foundation, 2023)
This study aimed to determine the influence of motivation and incentives on the performance of employees at the merchandise counter (salesperson) at PT. Matahari Department Store Mall of Serang, the authors use quantitative methods to carry out this research. The population in this study were employees at the Merchandise Counter (Pramuniaga) PT. Matahari Department Store Mall of Serang and for a population of 41 employees. In taking this sample, the writer uses a saturated sample, a sampling technique when all population members are used as samples, so the samples in this study are employees at the Merchandise Counter (Prafficker) PT. Matahari Department Store Mall of Serang has as many as 41 respondents. The study results obtained that motivation and incentives partially each have a significant effect on employee performance, and simultaneously motivation and incentives significantly affect employee performance at the merchandise counter (salesperson) at PT. Matahari Department Store Mall of Serang.